Analysis of 6004-2RSL SKF Bearing Inventory By Economic Order Quantity (EOQ) Method in Spart Part Division - Kartika, Hayu; Setia Bakti, Candra (Journal of Industrial Engineering & Management Research, 2020)
The Economic Order Quantity (EOQ) method is the quantity of inventory for one order with a minimum annual inventory cost. This method has several provisions such as determining the economical amount of raw materials, safety stock, and reorder points. With this method, the company can determine the frequency of spare parts purchases, the number of purchases, the optimal total purchase costs that minimize inventory costs, the number of safety stocks and reorder points. Based on the results of this study the most economical number of purchases for PT SI was 24.66 pcs. Then the optimal purchase frequency is 6 pcs, In addition based on the above calculation, it can be seen that safety stock is 4 pcs. According to the company safety stock method of 6 pcs, when compared with the research results of 4 pcs, it can be said that the savings result is 2 pcs. Then by using this method, the results of the total inventory cost of Rp. 119,560.04 are more efficient at Rp.58,196.96 when compared with the company's calculation of Rp.17,757.00 or can be said to use the EOQ method more efficiently by 32.73 percent.